Obstetrics and Gynecology Medicine: Go from Bench to Bedside - Stefano Canosa; Anna Maria Nuzzo (Life, 2025)
As we reach the conclusion of this Special Issue, Obstetrics and Gynecology Medicine: Go From Bench to Bedside, it is evident that the dynamic intersection between basic science and clinical practice continues to drive the evolution of care in women’s health [...]